A Phase II study of autologous mesenchymal stromal cells and c‐kit positive cardiac cells, alone or in combination, in patients with ischaemic heart failure: the CCTRN CONCERT‐HF trial. (13th April 2021) - Bolli, Roberto; Mitrani, Raul D.; Hare, Joshua M.; Pepine, Carl J.; Perin, Emerson C.; Willerson, James T.; Traverse, Jay H.; Henry, Timothy D.; Yang, Phillip C.; Murphy, Michael P.; March, Keith L.; Schulman, Ivonne H.; et al.
Abstract : Aims: CONCERT‐HF is an NHLBI‐sponsored, double‐blind, placebo‐controlled, Phase II trial designed to determine whether treatment with autologous bone marrow‐derived mesenchymal stromal cells (MSCs) and c‐kit positive cardiac cells (CPCs), given alone or in combination, is feasible, safe, and beneficial in patients with heart failure (HF) caused by ischaemic cardiomyopathy. Methods and results: Patients were randomized (1:1:1:1) to transendocardial injection of MSCs combined with CPCs, MSCs alone, CPCs alone, or placebo, and followed for 12 months. Seven centres enrolled 125 participants with left ventricular ejection fraction of 28.6 ± 6.1% and scar size 19.4 ± 5.8%, in New York Heart Association class II or III. The proportion of major adverse cardiac events (MACE) was significantly decreased by CPCs alone (−22% vs. placebo, P  = 0.043). Quality of life (Minnesota Living with Heart Failure Questionnaire score) was significantly improved by MSCs alone ( P  = 0.050) and MSCs + CPCs ( P  = 0.023) vs. placebo. Left ventricular ejection fraction, left ventricular volumes, scar size, 6‐min walking distance, and peak oxygen consumption did not differ significantly among groups. Conclusions: This is the first multicentre trial assessing CPCs and a combination of two cell types from different tissues in HF patients. The results show that treatment is safe and feasible. Even with maximal guideline‐directed therapy, both CPCs and MSCs were associated with improved clinical outcomes (MACE and quality of life, respectively) in ischaemic HF without affecting left ventricular function or structure, suggesting possible systemic or paracrine cellular mechanisms. Combining MSCs with CPCs was associated with improvement in both these outcomes. These results suggest potential important beneficial effects of CPCs and MSCs and support further investigation in HF patients. Abstract : Cardiovascular Cell Therapy Research Network: the CONCERT‐HF trial. CONCERT‐HF is the first multicentre trial assessing c‐kit positive cardiac cells (CPCs) and a combination of two cell types from different tissues in heart failure (HF) patients. Administration of autologous CPCs or mesenchymal stromal cells (MSCs) in patients with chronic ischaemic HF shows promising effects, namely, a reduction in hospitalization for HF and an improvement in quality of life, respectively, over the ensuing 12 months. Results of this Phase II study provide a rationale for additional clinical trials of cell therapy in chronic ischaemic HF.